Emphysematous Pyelonephritis Complicating an Undetected Diabetic Female: A Case Report - Rahim, Muhammad Abdur; Mitra, Palash; Zaman, Shahana; Uddin, Khwaja Nazim (Journal of Bangladesh College of Physicians and Surgeons, 2018)
A case of emphysematous pyelonephritis is reported here. A middle aged Bangladeshi lady presented with fever and left loin pain. She had tachycardia, dehydration and left renal angle tenderness. Investigations revealed diabetes mellitus, left renal stone and left sided emphysematous pyelonephritis complicated by acute kidney injury. She required nephrectomy along with antibiotics. Emphysematous pyelonephritis almost exclusively occurs in diabetic patients and rarely emphysematous pyelonephritis may unmask undetected diabetes as in the present case. Renal stone is also recognized risk factor for emphysematous pyelonephritis. J Bangladesh Coll Phys Surg 2018; 36(2): 80-81